The Impact of Inflation and Interest Rates on Economic Growth in Southeast Asia: A Panel Data Analysis - Samuel Eka Nathaniel; Bella Christine Princess Wantah; Zefanya Maureen Nathania; Michelle Angelique Nataputra; Ferdinand, Ferry Vincenttius (Universitas Pelita Harapan, 2025)
Economic growth in Southeast Asia is influenced by a variety of macroeconomic variables, with inflation and interest rates being two of the most crucial. This study aims to examine the impact of inflation and interest rates on the economic growth (measured by GDP) of ten Southeast Asian countries from 2007 to 2023. Using a panel data regression approach, the analysis applies several econometric models including Pooled OLS, Fixed Effects Model, Random Effects Model, and spatial econometric models (Spatial Autoregressive Model/SAR and Spatial Error Model/SEM) to determine the most suitable model for the data. The results show that interest rates have a significant negative effect on GDP growth, suggesting that higher interest rates tend to reduce economic activity in the region. Inflation, while showing a weaker relationship, also negatively affects GDP in most models. Spatial analysis further reveals the presence of spatial dependence among Southeast Asia countries, indicating that the economic performance of one country is not isolated but affected by its neighbors. Among the models tested, the Spatial Error Model (SEM) is found to be the best fit based on statistical criteria, highlighting the importance of unobserved regional factors and spatial spillover effects. Policy implications include the need for coordinated regional monetary policies, maintaining inflation within manageable limits, and enhancing economic cooperation among Southeast Asia nations. While the R-squared values are relatively low, the statistical significance of the core variables underscores their relevance. This study contributes to the broader understanding of macroeconomic management and regional economic integration in Southeast Asia.